2014
DOI: 10.1007/s10530-014-0828-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barred owl (Strix varia) range expansion on Haemoproteus parasite assemblage dynamics and transmission in barred and northern spotted owls (Strix occidentalis caurina)

Abstract: Effects of barred owl (Strix varia) range expansion on Haemoproteus parasite assemblage dynamics and transmission in barred and northern spotted owls (Strix occidentalis caurina)" (2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The ability of northern spotted owls to adapt to increased interspecific competition and direct predation may also be limited by genetic constraints arising from severe decreases in population size in some parts of the subspecies’ range (Funk et al , Forsman et al ). In addition, comparisons of blood parasite loads among barred owls and northern spotted owls found that northern spotted owls have greater parasite diversity and probability of infection than sympatric barred owls (Lewicki et al ). These findings support the enemy release hypothesis (Torchin et al ), where hosts (barred owls) benefit from a loss of parasites in their invasive range.…”
Section: Hypothesized Effects Of Barred Owlsmentioning
confidence: 99%
“…The ability of northern spotted owls to adapt to increased interspecific competition and direct predation may also be limited by genetic constraints arising from severe decreases in population size in some parts of the subspecies’ range (Funk et al , Forsman et al ). In addition, comparisons of blood parasite loads among barred owls and northern spotted owls found that northern spotted owls have greater parasite diversity and probability of infection than sympatric barred owls (Lewicki et al ). These findings support the enemy release hypothesis (Torchin et al ), where hosts (barred owls) benefit from a loss of parasites in their invasive range.…”
Section: Hypothesized Effects Of Barred Owlsmentioning
confidence: 99%
“…While there is ample evidence for the acquisition of native parasites by invasive host species (step 1 of parasite spillback; e.g. Miller and Vincent 2006;Georgiev et al 2014;Sheath et al 2015;Lewicki et al 2015), there is little conclusive evidence for an actual amplification and/or spillback to native species (but see Hershberger et al 2010;Goedknegt et al 2016). Finally, as an alternative mechanism to parasite spillback, incompetent invasive host species can act as a sink by diluting the native parasite population and thereby reducing the disease risk for native species (transmission interference or parasite dilution; Thieltges et al 2009;Paterson et al 2011;Poulin et al 2011;Goedknegt et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a recent but closely related invader to the west coast, barred owls have the potential to bring novel, harmful pathogens and parasites from east coast populations, which could be transmitted to spotted owls and may be more lethal to the native species. As such, Lewicki et al () examined the Haemoproteus blood parasite assemblages of barred owls in their native and invasive ranges and in northern spotted owls. They reported that northern spotted owls had a slightly lower prevalence of Haemoproteus infection than both populations of barred owls, but mean infection intensity was almost 100 times greater than that of barred owls in the West.…”
Section: Resultsmentioning
confidence: 99%